2017
DOI: 10.1111/ajco.12757
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of head and neck cancer in Thailand

Abstract: Cancer is the most common cause of death in Thailand, with the mortality almost doubled during 1998-2011 (from 48.4 to 95.2 per 100 000). The estimated number of new cancer cases in 2011 was 112 392. Our review provides baseline data on the current epidemiological situation with head and neck (HN) cancer in Thailand based on reports of the National Cancer Registry and findings from local and international publications. Collectively, HN cancer approaches agestandardized rate (ASR) incidence of 15.7 and 10.7 per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 24 publications
3
55
0
Order By: Relevance
“…For major salivary gland, the commonest histopathology is mucoepidermoid carcinoma, while for thyroid cancer the commonest is papillary thyroid cancer. Similar findings are reported by these studies [15,31].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For major salivary gland, the commonest histopathology is mucoepidermoid carcinoma, while for thyroid cancer the commonest is papillary thyroid cancer. Similar findings are reported by these studies [15,31].…”
Section: Discussionsupporting
confidence: 92%
“…The males are three times more prone than females for laryngeal, hypopharyngeal and oropharyngeal. This is similar to other studies as reported by Bhattacharjee et al [17]; Shunyu and Syiemlieh [6]; Tangjaturonrasme et al [15]; Delagranda et al [18]; Taziki et al [16]. This could be attributed mainly to the abuse of risk factors, such as tobacco, betel nut and alcohol consumption, where these risk factors were two times more prevalent in males than in females.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Nasopharyngeal carcinoma (NPC) is endemic to Southern China, the Middle East, Alaska, Greenland and Southeast Asia, including Thailand (1,2). Concurrent chemoradiotherapy (CCRT) with high-dose cisplatin followed by three cycles of adjuvant chemotherapy (CT) containing cisplatin plus 5fluorouracil is considered the standard protocol for patients with locally advanced nasopharyngeal carcinoma (LA-NPC), based upon the significant survival benefits demonstrated by the Intergroup (INT) 0099 study (3).…”
Section: Introductionmentioning
confidence: 99%
“…5.1 per 100,000 of the male and female populations, respectively. 7 In some cases, either open or endoscopic thyroid surgery is necessary. [8][9][10] Patients with thyroid diseases are affected by the fluctuations in thyroid hormone levels, resulting in abnormal symptoms (e.g., dry skin, hair loss, irregular menstruation, and bradycardia), mental disorders (e.g., depression, loss of memory, and insomnia), and decreased quality of life.…”
mentioning
confidence: 99%